How late can you update gaze-contingent multi-resolutional displays without detection? - Loschky, Lester C.; Wolverton, Gary S. (ACM, 2007)
This study investigated perceptual disruptions in gaze-contingent multi-resolutional displays (GCMRDs) due to delays in updating the center of highest resolution after an eye movement. GCMRDs can be used to save processing resources and transmission bandwidth in many types of single-user display applications such as virtual reality, video-telephony, simulators, and remote piloting. The current study found that image update delays as late as 60 ms after an eye movement did not significantly increase the detectability of image blur and/or motion transients due to the update. This is good news for designers of GCMRDs, since 60 ms is ample time to update many GCMRDs after an eye movement without disrupting perception. The study also found that longer eye movements led to greater blur and/or transient detection, due to moving the eyes further into the low-resolution periphery, effectively reducing the image resolution at fixation prior to the update. In GCMRD applications where longer saccades are more likely (e.g., displays with relatively large distances between objects), this problem could be overcome by increasing the size of the region of highest resolution.
Keywords: Eye movements; Saccades; Fixation; Gaze-contingent multi-resolutional displays; Area of interest; Gaze-contingent displays